A Bayesian Approach to Aggregate Planning Oriented to Retail Marketing - Taquía-Gutiérrez, José Antonio (2015)
The need to generate efficiencies in volume purchases or improve the accuracy of sales forecasts is based on integration efforts within organizations competing in retail channel pursuing gain market share. Long-term planning is usually restricted to a strategic planning guidelines, foresight scenarios or trade policies where the uncertainty of different variables generates little influence on tactical level planning. This article discusses the contribution of the Bayesian approach used to improve tactical planning in a highly dynamic environment due to the influence of changes in business strategies of medium and short term as usually occurs in retail marketing environment.